Parkett : The Parkett series with contemporary artists (Zürich : Parkett-Verlag, 2002)
Table of Content The Mobile Muse by Thyrza Nicholas Goodeve & Giuliana Bruno Angela Bulloch Angela Bulloch’s Digital Reductions by Juliane Rebentisch Maybe by Andrew Wilson The Simulation of Simulation (and vice versa) by Martin Prinzhorn Daniel Buren From Painting to Architecture by Anne Rorimer Sumultanément, 2002, Photo Insert by Marin Kasimir The Decorative Strategy in Daniel Buren’s Le Musée qui n’existait pas by Alison M. Gingeras Conversation between Daniel Buren & Pierre Huyghe Daniel Buren, DE LA BRODERIE À LA DENTELLE, travail in situ Pierre Huyghe Traveler’s Tales by Jeremy Millar The Tale of the One Thousand Signs by Hans Ulrich Obrist Pierre Huyghe’s Ellipses by Robert Hobbs Fish Scales, Allan Sekula’s TSUKIJI by Edward Dimendberg Tripe under Attack, Les Infos du Paradis by Roberto Ohrt A Museum of Lies, Cumulus from America by Nato Thompson Art, Science and the True Mistakes of Metaphor, Cumulus from Europe by Greg Hilty
﻿This volume of Parkett may be taken as an invitation to roam through space: Angela Bulloch, Daniel Buren and Pierre Huyghe probe unexplored potential in works of art that betoken acts of piercing, stretching and occupation. Even some of the pages themselves, with their unusual perforations, explicitly echo Buren’s most recent architectural interventions. Yet categories like painting, sculpture and architecture, or abstraction and fiction are losing their fixity, dissolving in ambiguities, overlappings and also displacement, as analyzed in the conversation between Daniel Buren and Pierre Huyghe. (editorial by publisher)
boek
Keywords: Bulloch, Angela; Huyghe, Pierre; Buren, Daniel